Os lugares da sociologia na formação de estudantes do ensino médio: as perspectivas de professores - Kelly Cristine Corrêa da Silva Mota (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2005)
This article presents the results of research on the teaching of sociology in secondary schools. Its purpose is tounderstand the place of sociologicalknowledge in the formation ofsecondary school students based on theperspective of teachers of sociology.Theoretical studies, the analysis of le-gal documents and interviews withteachers pointed to sociologicalknowledge as a fundamentalcomponent in the formation of criticalstudents and citizens. Theproblematisation of this argument,starting from a broad criticalconception of education andcitizenship, suggests that teaching inthis field is directed by thepresupposition of schooling and thelack of preparation on the part ofstudents to exercise citizenshipcritically. The sociology taught inschools, perceived as a privilegedelement in the constitution of thesedimensions, ends up by underlining theyoung peoples supposed lack ofpreparation, interest and politicalcapacity for the exercise of thisactivity. In addition, it ignores otherpractices and social spaces which leadthe human being to a critical formationfor citizenship.